2019
DOI: 10.1111/jocd.13184
|View full text |Cite
|
Sign up to set email alerts
|

Effects of different therapeutic modalities for postacne scars on circulating collagen III

Abstract: Background Therapies for postacne scarring act through modulation of elastin and collagen, and collagen III might therefore represent a biomarker of treatment effectiveness. Patients and methods Patients (n = 70) with postacne scars and individuals without scars (n = 56) were included in this case‐control study. Patients were treated with Dermaroller microneedling, trichloroacetic acid chemical reconstruction, punch excision, or scar subcision. Scar severity was graded immediately before and after treatment wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“… 48 CROSS induces neosynthesis of collagen and elastin and has proven to be an effective standalone treatment for ice pick acne scarring. 49 , 50 TCA and phenol CROSS were found to be safe and effective when used in conjunction with subcision for atrophic scarring across all studies evaluated, but it was noted that TCA may cause widening of scars if applied improperly. The majority of studies showed marked improvement in combinatorial subcision and CROSS treatments in patients presenting with a mixture of ice pick, rolling, and boxcar scars, except for one split-face study by Kamel et al where TCA did not provide an additional clinical benefit.…”
Section: Combinatorial Treatmentsmentioning
confidence: 99%
“… 48 CROSS induces neosynthesis of collagen and elastin and has proven to be an effective standalone treatment for ice pick acne scarring. 49 , 50 TCA and phenol CROSS were found to be safe and effective when used in conjunction with subcision for atrophic scarring across all studies evaluated, but it was noted that TCA may cause widening of scars if applied improperly. The majority of studies showed marked improvement in combinatorial subcision and CROSS treatments in patients presenting with a mixture of ice pick, rolling, and boxcar scars, except for one split-face study by Kamel et al where TCA did not provide an additional clinical benefit.…”
Section: Combinatorial Treatmentsmentioning
confidence: 99%